Feature Analysis and Detection Techniques for Piracy Sites - Choi, Seul Ki; Kwak, Jin (KSII Transactions on Internet and Information Systems, 2020)
In recent years, digital content has become easily accessible because of internet technology. Representative examples of such digital content include various types, such as music, TV, (program, sport, drama etc.) and films. However, there are cases where internet technology is used in illegal ways without the authorization of the copyright holder for digital content. Such actions have a direct impact on copyright owners' profits and further affect the development of the digital culture industry adversely. Therefore, in this study, we analyze features to detect piracy sites that cause copyright infringement. Further, we develop a piracy site detection crawler based on these features and present the analysis of its performance.
Keywords: Copyright holders; Copyright infringement; Digital contents; Digital culture; Direct impact; Feature analysis; Internet technology; Site detection; Copyright; Infringement; Piracy sites